Imunomarcação dos receptores de EGF (EGFR e c-ErbB2) no carcinoma de células escamosas em cães - Magalhães, Paula Lima (2017)
Squamous cell carcinoma (SCC) is one of the most common malignant cutaneous tumors in all species, as well as in the human species, ranging from young animals to the elderly. It has development associated with environmental factors such as prolonged exposure to solar rays and epidermal hypopigmentation. According to the literature, 80% of malignancies originate in environmental stimuli, due to exposure to carcinogens. Despite the multifactorial etiology, the search for clarification of the causes and mechanisms of cancer evolution must be incessant, since innumerable neoplasms can be prevented, especially when induced by exogenous factors. The aim of this study was to study canine cutaneous SCC in the light of different histomorphological patterns of the neoplasia, evaluating its immunophenotype response to EGFR and c-erbB2 epidermal growth factor receptors. For that, the cases of canine SCC were analyzed from the archive of the Animal Pathology Sector of the EVZ / UFG from 2006 to 2015. For the epidemiological study, registration information was considered, including breed, sex, age and anatomical location. Regarding the histomorphological evaluation and malignancy criteria, the lesions were classified according to the system recommended by the Müller e Kirk’s. Anti-EGFR (HER1) and anti-c-erbB-2 (HER2) antibodies were used for the immunohistochemical study to better understand the role of these proteins in the mechanisms involved in the genesis, proliferation and evolution of SCC in dogs. Considering the histomorphological and immunophenotypic analyzes, the correlation between its variables was tested, and a correlation was verified between the EGFR immunostaining and the degree of SCC differentiation (r = 0.26, p = 0.02). On the other hand, there was no correlation between c-erbB2 immunostaining and histomorphological differentiation (r = 0.02; p = 0.83). When the correlation between EGFR and c-erbB2 immunoblots was tested, a positive correlation was also observed, but not statistically significant (r = 0.21, p = 0.06). It is concluded that there is a propensity that the increase in EGFR immunoexpression is directly proportional to the degree of SCC differentiation, and that it does not occur with c-erbB2 immunostaining. Also, SCCs in dogs seems to exhibit simultaneous increase of EGF receptor immunostaining.